Income inequality in Sri Lanka, 1953-97: structure, trends and factors - Karunaratne, H.D. (My University, 2000)
Using decomposable inequality measurements and shift share analysis, this study analyzes the structure and trends of income inequality in Sri Lanka and factors affecting it during the 1953-1997 period. Three main relative income inequahty phases appeared: (1) decreasing inequality during 1953-1973 due to strong government intervention in the economy, (2) increasing inequality during 1973-1987, regardless of policy change. (3) decreasing inequality during 1987-1997, even under the continuation of privatization and deregulation programs. These three phases of inequality were similar in terms of spending units, income receivers and individuals and were consistent with the existing literature. Ten typically cited causes of the trends in income inequality are examined for income receivers, namely, (1) age, (2) gender, (3) community, (4) level of education, (5) industry, (6) factor incomes, (7) types of income (money income and income in kind), (8) sector, (9) region, (10) economic growth and stmctural changes. Among these causes (1) to (7) are analyzed at sectoral, regional and national levels. Spending-unit, and individual based data were also used as much as possible to explore inequality structure, trends and factors. , TlTjroughout the 1963-1997 period, income receivers' location by sector, level of education, and sources of income in terms of factor, industry and types of income, were the main determinants of level and trends of income inequality in Sri Lanka. Some other factors were influential in deteimining level and trends of income inequality in different inequality phases. These findings are consistent with the three other existing inequality decomposition studies conceming Sri Lanka; Glewwe (1986, and 1988) and Terasaki (1993). even they used completely different data sources and income units.